A contribution to knowledge of Procloeon Bengtsson, 1915 from the Chinese mainland (Ephemeroptera: Baetidae) with description of a new species - Chen, Xiao-Fang; Zhou, Chang-Fa (Zootaxa, 2023)
The mayflies of the genus Procloeon Bengtsson, 1915 are common insects in China. However, partially because of its complicated taxonomic history and numerous species, this genus has never been revised locally in China. Here, we review all reported and related species from the Chinese mainland and confirmed three species of Procloeon occurred namely, Procloeon pennulatum (Eaton, 1870) (= Centroptilum henanensis Zhou et al., 1997, syn. n.) distributed in northern China, P. chinensis (She et al., 1995) (comb. nov.) from southern China and P. strumiferum sp. n. found in eastern China. The imagoes of the new species lack a costal projection of the hindwings but the gills I–V of the nymphs have double lamellae. In contrast, both the former species have costal process in the hindwings and double lamellae of gills I–VI. The three species can all be differentiated by imaginal genitalia and nymphal color. This revision clarifies all historical species in the genus Procloeon and Centroptilum from the Chinese mainland and provides a base for further research.